THE CORRELATION BETWEEN STUDENTS’ INTEREST OF READING AND WAYS OF LEARNING TOWARD READING COMPREHENSION AMONG THE SECOND GRADE STUDENT OF SMAN 4 KEDIRI - Fitriani, Tika Wahyu (LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
The aim of this study was to find out the correlation between the interest of reading and ways of learning toward reading comprehension among the second grade students’ of SMAN 4 Kediri. The quantitative approach was used to design this research. The techniques were partial correlation and simultaneous correlation. The instruments were questionnaires and test. The subject of this research was the second grades students while the sample of this research was 92 students from 120 populations. The result is The interest of reading belongs to fair category ; The ways of learning of the students belong to good category ; The reading comprehension belongs to very good category. Partially, the value of correlation between the ways of learning and reading comprehension is 0.340 or 34.0% with the significance level is 0.001 Moreover, the value of correlation between interest in reading and reading comprehension is 0.235 or 23.5% with the significance level is 0.025. Simultaneously shows that the interest of reading and the ways of learning are a significant predictor of reading comprehension the significant value is 0.000. It means that there is strong positive simultaneous significant correlation.